PENGARUH PEMBERIAN JUS ALPUKAT (PERSEA AMERICANA [MILL]) TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL TM II DI PUSKESMAS SINDANG KABUPATEN INDRAMAYU - Feriyal Bawazir (JURNAL KESEHATAN INDRA HUSADA, 2019)
Anemia occurs worlwide, especially in developing countries and in low socioeconomic groups. i.e. in 45% of women. Anemia is one of the causes of bleeding. Various attempts have been made, but have not shown the maximum results. Need other efforts in the nutrition form of avocado juice to overcome the anemia of pregnancy. This research aims to determine the effect of avocado juice on hemoglobin levels of pregnant women. The type of this research is Quasi Experimental design which implemented in November to December 2017 with 33 respondents of trimester II pregnant women who have HB<11g/dL and determined by purposes sampling. Repondents filled out questionnaires to determine their characteristics and performed laboratorium checkup 3 times, pre, on day 7 and 14 after intervention. The result of the research shows that Hb level average of control groups is p=0.441, whileHb level average of intervention group is p=0.043. It concludes that there was a positive effect of consuming avocado juice for 14 days in increasing the average of Hb levels